2006
DOI: 10.1158/0008-5472.can-06-1000
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Human Colorectal Tumor Cells to Treatment with the Anti–Epidermal Growth Factor Receptor Monoclonal Antibody ICR62 Used Alone and in Combination with the EGFR Tyrosine Kinase Inhibitor Gefitinib

Abstract: The anti-epidermal growth factor receptor (EGFR) monoclonal antibody cetuximab has been approved for the treatment of patients with metastatic colorectal cancer. However, there is currently no reliable marker for response to therapy with the EGFR inhibitors. In this study, we investigated the sensitivity of 10 human colorectal tumor cell lines (DiFi, CCL218, CCL221, CCL225, CCL227, CCL228, CCL231, CCL235, CCL244, and HCT-116) to treatment with our anti-EGFR monoclonal antibody, ICR62, and/or the EGFR tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…Our data show that cetuximab can block EGF binding to its receptor in both sensitive and resistant cell lines, thus reducing ERBB1-phosphorylation, an observation that has been reported previously with anti-ERBB1 antibodies in CRC, head/neck squamous, and nonsmall cell lung cancer cell lines (21,29). EGFinduced downstream ERK1/2 phosphorylation was incompletely abolished by 20 μg/mL of cetuximab in vitro, a concentration, however, that is likely to be much higher than that present in a tumor in a clinical setting.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data show that cetuximab can block EGF binding to its receptor in both sensitive and resistant cell lines, thus reducing ERBB1-phosphorylation, an observation that has been reported previously with anti-ERBB1 antibodies in CRC, head/neck squamous, and nonsmall cell lung cancer cell lines (21,29). EGFinduced downstream ERK1/2 phosphorylation was incompletely abolished by 20 μg/mL of cetuximab in vitro, a concentration, however, that is likely to be much higher than that present in a tumor in a clinical setting.…”
Section: Discussionsupporting
confidence: 87%
“…These data further support the use of a wellcharacterized panel of cell lines to determine clinically relevant molecular markers (16)(17)(18)(19). The large number of cell lines in our panel explains why we have found an association with KRAS in contrast to other CRC cell line studies (20,21). We have also demonstrated that the direct effects of cetuximab are largely replicated with lapatinib, lending support to its potential role as an alternative form of therapy.…”
Section: Discussionsupporting
confidence: 77%
“…We found that, with the exception of the EGFR overexpressing cell line, DiFi, which was highly sensitive to treatment with both ICR62 and gefitinib, treatment with a combination of ICR62 and gefitinib did not enhance the growth inhibitory effect of the single agent in DiFi cells nor did it sensitize colorectal tumour cells that were insensitive to treatment with the single agent (20). The aim of this study was to evaluate the sensitivity of these colorectal tumour cell lines to treatment with afatinib (BIBW2992), an irreversible erbB family blocker (21-28) currently used in phase III clinical trials, and various cytotoxic drugs.…”
Section: Introductionmentioning
confidence: 80%
“…We have previously investigated the growth response of a panel of human colorectal tumour cell lines to treatment with our anti-EGFR mAb, ICR62, used alone and in combination with the reversible EGFR TKI, gefitinib (20). We found that, with the exception of the EGFR overexpressing cell line, DiFi, which was highly sensitive to treatment with both ICR62 and gefitinib, treatment with a combination of ICR62 and gefitinib did not enhance the growth inhibitory effect of the single agent in DiFi cells nor did it sensitize colorectal tumour cells that were insensitive to treatment with the single agent (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation